Prediction of training intesity from maximal running speed : "can it be that simple?" - Reynolds, Ezekial K. (My University, 2012)
Determining absolute values for training intensity often requires laboratory evaluation, impractical beyond the setting of elite athletes. PURPOSE: This study defined physiologic thresholds (ventilatory threshold (VT) & respiratory compensation threshold (RCT)) as simple percentages of maximal running velocity, and then cross validated the accuracy of the predictive equation. METHODS: Thirty-one well trained students performed incremental, maximal treadmill running with respiratory metabolism measured via open circuit spirometry. The speed at VT and RCT were determined by visual inspection of each individual test. Predictive equations representing the lower and upper 95% confidence interval for VT and RCT, respectively, were developed using linear regression. Twenty independent subjects performed the same incremental, maximal exertion test to determine maximal velocity. They then performed two 30 minute submaximal treadmill bouts at percentages of maximal velocity, defined in the predictive equation, to determine if the predicted velocity could produce conditions consistent with <VT and >RCT. RESULTS: In the validation phase for VT and RCT, respectively, <64% and >86% of maximal speed produced exercise intensity <VT and >RCT, respectively. CONCLUSION: VT and RCT can be predicted from simple percentages of the maximal running speed with reasonable accuracy, and may provide a simplified method of training prescription.
Keywords: Athletic Performance.; Exercise tests.; Physical fitness.